2001
DOI: 10.1007/bf02994009
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Integration of Foreign DNA Into a Defined Locus on Chromosome 19 in K562 Cells Using AAV-Derived Components

Abstract: Targeted integration of foreign DNA is ideal for gene therapy, particularly when target cells such as hematopoietic cells actively divide and proliferate. Adeno-associated virus (AAV) has been shown to integrate its genome into a defined locus, AAVS1 (19q13.3-qter). The inverted terminal repeat (ITR) and Rep proteins are responsible for this site-specific integration, and a system has been developed that delivers a gene preferentially into AAVS1 by using these components of AAV. We examined whether this system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Similar results were seen using cationic liposome-mediated transfection [Kogure et al, 2001;Lamartina et al, 1998;Satoh et al, 2000;Tsunoda et al, 2000;Young, Xiao, and Samulski, 2000] or electroporation [Kogure et al, 2001].…”
Section: Plasmid-based Gene Delivery Systemssupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results were seen using cationic liposome-mediated transfection [Kogure et al, 2001;Lamartina et al, 1998;Satoh et al, 2000;Tsunoda et al, 2000;Young, Xiao, and Samulski, 2000] or electroporation [Kogure et al, 2001].…”
Section: Plasmid-based Gene Delivery Systemssupporting
confidence: 80%
“…Preferential integration, using plasmid-based systems has been demonstrated in cell lines derived from human embryonic kidney cells, human erythroid leukemia cells, a human cervical carcinoma and a human hepatocarcinoma [Balagué, Kalla, and Zhang, 1997;Kogure et al, 2001;Lamartina et al, 1998;Pieroni et al, 1998;Rinaudo et al, 2000;Satoh et al, 2000;Surosky et al, 1997;Young, Xiao, and Samulski, 2000]. The major problem with transfection is that it tends to be much less efficient than virus particle-mediated gene transfer, especially for delivery to intact organs.…”
Section: Plasmid-based Gene Delivery Systemsmentioning
confidence: 97%
“…To this end, AAV-based site-directed integration systems may be useful, because Rep proteins from AAV facilitate the integration of the viral genome into a specific locus (termed AAVS1) in chromosome 19. 26 This locus is one of the safe locations in the human genome for efficient and safe transgene expression. 27 Ammar et al 28 demonstrated that fusion constructs consisting of Rep and Tol2 transposase integrated marker genes from Tol2 transposon donor plasmids near the AAVS1 locus, which may offer a safer transposon-based gene delivery system for human gene and cell therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The list indirectly demonstrates that no 'ideal' vector yet exists. New technology, including small interference RNA (siRNA), 31 adeno-associated virus inverted terminal repeat (AAV ITR)-based plasmids, 32,33 novel classes of lentivirus (equine infectious anemia virus-EIAV; feline immunodeficiency virus-FIV), [34][35][36][37][38][39][40] lentivirus-herpesvirus hybrids and other viral vectors is in development, but their efficiency has yet to be reported in the context of Figure 1 Multistep process of insulitis. During ontogeny, a population of thymocytes whose TCR recognize b-cell-specific antigens are either not deleted in the thymus, or fail to be tolerized subsequently, in the periphery.…”
Section: Type I Diabetes Mellitus: the Autoimmune Processmentioning
confidence: 99%